Strategic groups as subsets of strategic scope groups in the Belgian brewing industry - Houthoofd, Noël; Heene, Aimé (Strategic Management Journal, 1997)
This research report proposes a distinction between strategic scope groups and strategic groups whereby strategic groups are delineated within strategic scope groups. A strategic scope group (SSG) includes firms within an industry that define their business using a four-dimensional ‘strategic space’ consisting of buyer types, product types, geographical reach and level of vertical integration, in a similar way. Within each SSG there may be several strategic groups (SGs). An SG includes firms within an SSG that deploy their resources in a similar way and that compete in the same way. While all firms within an SSG may compete against each other, firms within the same SG compete against each other in a similar way. Within the brewing industry in Belgium five SSGs could be identified. These SSGs differ statistically significantly on a risk-adjusted return on assets measure. SGs themselves did not differ on this performance measure. One may therefore conclude that mobility barriers between SSGs are higher than they are between SGs. © 1997 by John Wiley & Sons, Ltd.